LICARA nanoSCAN - A tool for the self-assessment of benefits and risks of nanoproducts. (May 2016) - van Harmelen, Toon; Zondervan-van den Beuken, Esther K.; Brouwer, Derk H.; Kuijpers, Eelco; Fransman, Wouter; Buist, Harrie B.; Ligthart, Tom N.; Hincapié, Ingrid; Hischier, Roland; Linkov, Igor; Nowack, Bernd; Studer, Jennifer; et al.
Abstract: The fast penetration of nanoproducts on the market under conditions of significant uncertainty of their environmental properties and risks to humans creates a need for companies to assess sustainability of their products. Evaluation of the potential benefits and risks to build a coherent story for communication with clients, authorities, consumers, and other stakeholders is getting to be increasingly important, but SMEs often lack the knowledge and expertise to assess risks and communicate them appropriately. This paper introduces LICARA nanoSCAN, a modular web based tool that supports SMEs in assessing benefits and risks associated with new or existing nanoproducts. This tool is unique because it is scanning both the benefits and risks over the nanoproducts life cycle in comparison to a reference product with a similar functionality in order to enable the development of sustainable and competitive nanoproducts. SMEs can use data and expert judgment to answer mainly qualitative and semi-quantitative questions as a part of tool application. Risks to public, workers and consumers are assessed, while the benefits are evaluated for economic, environmental and societal opportunities associated with the product use. The tool provides an easy way to visualize results as well as to identify gaps, missing data and associated uncertainties. The LICARA nanoSCAN has been positively evaluated by several companies and was tested in a number of case studies. The tool helps to develop a consistent and comprehensive argument on the weaknesses and strengths of a nanoproduct that may be valuable for the communication with authorities, clients and among stakeholders in the value chain. LICARA nanoSCAN identifies areas for more detailed assessments, product design improvement or application of risk mitigation measures. Graphical abstract: Highlights: The paper introduces the new web based tool for SMEs named LICARA nanoSCAN. It is the first methodology to assess both benefits and risks of nanoproducts. It enables laymen to assess a product and deal with data paucity and uncertainty. It is based on Risk Assessment and Life Cycle Assessment using no quantitative data. An example on carbon nanotubes in fuel cells and test results are presented.